Antistatic waterborne polyurethane floor slurry and preparation method thereof
By preparing anti-static water-based polyurethane floor slurry, and cross-linking and composite using nano-anti-bacterial anti-static fibers and anti-bacterial anti-static fillers, the lack of performance of existing epoxy self-leveling anti-static floor materials is solved, and the floor coating with excellent conductivity, anti-bacterial, wear resistance and mechanical properties is achieved.
Patent Information
- Application Number
- CN202510054037.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-01-14
AI Technical Summary
The existing epoxy self-leveling anti-static floor materials have problems such as poor antibacterial properties, low hardness, poor wear resistance, insufficient mechanical properties and poor environmental protection, and their application range is limited.
A method of preparing anti-static water-based polyurethane floor slurry is adopted to form a coating with excellent conductivity, anti-bacterial, wear resistance and mechanical properties through the preparation of nano-anti-bacterial anti-static fibers, the preparation of anti-bacterial anti-static filler dispersion, and the cross-linking and composite of aqueous polyurethane and anti-bacterial anti-static filler.
It has achieved anti-static floor coatings with high conductivity, high antibacterial properties, good wear resistance and excellent mechanical properties, and is suitable for most scenario areas.
Smart Images

Figure CN119463684B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of floor coatings, and in particular to an antistatic waterborne polyurethane floor slurry and a preparation method thereof. Background Art
[0002] With the continuous development of science and technology and the advancement of industrialization, static electricity problems have become increasingly prominent in modern industrial production and daily life, especially in the fields of electronics, precision instruments, medicine, clean rooms, etc. The prevention and control of static electricity problems is particularly important. The accumulation and discharge of static electricity can have serious effects on equipment and products, and even cause safety hazards such as fire and explosion. Therefore, the research and development and application of anti-static materials have become one of the core needs in these fields.
[0003] The generation of static electricity discharge usually comes from the accumulation and rapid release of static electricity, especially in a dry environment. Physical phenomena such as friction, contact, and separation can easily lead to the generation and accumulation of static electricity. Among them, the floor is more likely to accumulate static electricity due to frequent friction, which poses a great safety hazard. The anti-static floor slurry is coated on the floor surface to form a layer of highly conductive coating, thereby avoiding the accumulation of static electricity and eliminating the hazards caused by static electricity.
[0004] Epoxy self-leveling anti-static floor is one of the most common anti-static floor materials currently. It is widely used in electronic workshops, clean rooms, laboratories and other environments with strict control requirements for static electricity. The basic principle is to add a certain proportion of conductive fillers (such as carbon black, metal powder, etc.) to the epoxy resin matrix so that the floor surface can form a conductive network, effectively conduct away static charges and prevent static electricity accumulation. However, epoxy self-leveling anti-static floor has some limitations, such as poor antibacterial properties, low hardness, poor wear resistance, insufficient mechanical properties and poor environmental protection, and its application range is small. Summary of the invention
[0005] In order to solve the above-mentioned technical defects, the present invention has developed a method for preparing an anti-static water-based polyurethane floor slurry. The prepared floor slurry has the characteristics of high conductivity, high antibacterial property, good wear resistance and excellent mechanical properties after forming a coating, and can be applied to most scenarios.
[0006] A method for preparing an antistatic waterborne polyurethane floor slurry comprises the following steps:
[0007] S1: Preparation of nano antibacterial and antistatic fibers;
[0008] After N,N-dimethylformamide and anhydrous ethanol are uniformly mixed, 2-aminoterephthalic acid is added, and then tetrabutyl titanate is added for ultrasonic dispersion, heated and washed, and then dried to obtain amino-modified Ti-MOF, polydopamine is dissolved in N,N-dimethylformamide, benzoyl acetone copper and amino-modified Ti-MOF are added, ultrasonically dispersed and stirred, and then electrostatic spinning and high-temperature carbonization are performed in sequence to obtain nano antibacterial and antistatic fibers;
[0009] S2: preparing antibacterial and antistatic filler dispersion;
[0010] Add guar gum to deionized water in an ice water bath, then add methacryloyl chloride, then transfer to room temperature for stirring, and dry to obtain modified guar gum, ultrasonically disperse nano antibacterial antistatic fiber and polyvinyl pyrrolidone in deionized water, then add modified guar gum for ultrasonic dispersion to obtain antibacterial antistatic organic filler dispersion;
[0011] S3: Cross-linked composite of waterborne polyurethane and antibacterial and antistatic filler;
[0012] Mix castor oil and isophorone diisocyanate and let stand, then add 2,2-dihydroxymethylbutyric acid and stir. After cooling, add triethylamine and stir. Then add it to the antibacterial and antistatic organic filler dispersion and stir evenly. Then add ethylenediamine, defoaming agent and wetting agent, and stir at high speed to obtain an antistatic waterborne polyurethane floor slurry.
[0013] Furthermore, step S1 of preparing the nano antibacterial and antistatic fiber comprises the following steps:
[0014] S1.1: N,N-dimethylformamide and anhydrous ethanol are mixed in a container at a volume ratio of 1: (1-1.05), stirred at a stirring speed of 200-250 rpm, and then 4-6 wt% of 2-aminoterephthalic acid is added. After stirring for 20-30 minutes, tetrabutyl titanate is added, and then placed in an ultrasonic disperser, ultrasonically dispersed at an ultrasonic frequency of 25-30 kHz for 10-15 minutes, and then heated in an oven at 150-155 ° C for 18-20 hours, washed with N,N-dimethylformamide and anhydrous ethanol for 2-3 times, and then rotary evaporated to obtain amino-modified Ti-MOF;
[0015] S1.2: 6-8 parts of polydopamine and 50-60 parts of N,N-dimethylformamide are placed in a container and stirred until the polydopamine is completely dissolved, and then 8-10 parts of copper benzoyl acetone and 12-15 parts of amino-modified Ti-MOF are added, and ultrasonic dispersion is performed in an ultrasonic disperser at an ultrasonic frequency of 35-40 kHz for 8-10 minutes, and then magnetic stirring is performed at a rotation speed of 150-200 rpm for 6-8 hours to obtain a metal organic spinning solution;
[0016] S1.3: Load the metal organic spinning solution into the injection pump of the electrospinning machine, adjust the distance between the needle of the injection pump and the aluminum foil receiving plate to 10-15cm, and then perform electrospinning at a working voltage of 12-15kV and a spinning speed of 0.02-0.03mm / min, collect the metal organic nanofiber membrane on the aluminum foil receiving plate, put it into an oven and dry it at 75-80℃ for 10-12 hours, then place it in a tubular furnace, introduce 85-90% nitrogen gas of the tubular furnace volume into the tubular furnace and adjust the temperature to 200-250℃, heat for 1-1.5 hours, then heat to 850-900℃ at a heating rate of 8-10℃ / min, and keep warm for 40-50 minutes to obtain nano antibacterial and antistatic fibers.
[0017] Furthermore, step S2 prepares an antibacterial and antistatic organic filler dispersion, comprising the following steps:
[0018] S2.1: 15-20 parts of deionized water are placed in a container, and then placed in an ice water bath at 2-4°C, 3-4 parts of guar gum are added and stirred evenly, and then 1-1.5 parts of methacryloyl chloride are slowly added, and after transferring to room temperature, stirring at a stirring speed of 100-120 rpm for 18-20 hours, and then drying in an oven at 70-75°C to obtain modified guar gum;
[0019] S2.2: Mix 4-6 parts of nano antibacterial antistatic fiber and 1-1.5 parts of polyvinyl pyrrolidone and place them in a container, add 120-150 parts of deionized water and stir evenly, then add and place in an ultrasonic homogenizer, perform ultrasonic treatment at an ultrasonic power of 400-500W for 20-25 minutes to obtain a nano antibacterial antistatic fiber dispersion, then add 2-3 parts of modified guar gum to the nano antibacterial antistatic fiber dispersion, continue to perform ultrasonic treatment at an ultrasonic power of 600-800W for 8-10 minutes to obtain an antibacterial antistatic organic filler dispersion.
[0020] Furthermore, step S3 of cross-linking and compounding the waterborne polyurethane and the antibacterial and antistatic filler comprises the following steps:
[0021] S3.1: 40-42 parts of castor oil and 13-13.5 parts of isophorone diisocyanate are uniformly mixed and allowed to stand at 85-90°C for 2-2.5 hours, and then 2.5-3 parts of 2,2-dihydroxymethylbutyric acid are added and stirred for 3-3.5 hours, and then the temperature is lowered to 45-50°C, and then 2-2.3 parts of triethylamine are added and stirred for 32-40 minutes to obtain a reaction solution;
[0022] S3.2: Add the reaction solution obtained in step S3.1 to the antibacterial and antistatic organic filler dispersion obtained in step S2.2 and stir evenly, then add 0.8-1 parts of ethylenediamine, 0.05-0.1wt% of defoaming agent and 0.1-0.3wt% of wetting agent, place in a basket grinder and stir at a speed of 1800-2000rpm for 1-1.5 hours to obtain an antistatic waterborne polyurethane floor slurry.
[0023] Furthermore, the volume of tetrabutyl titanate added in step S1.1 accounts for 2.5-3% of the total volume of N,N-dimethylformamide and anhydrous ethanol.
[0024] Furthermore, in step S1.3, the inner diameter of the syringe pump needle is 0.4-0.5 mm.
[0025] Furthermore, in step S2.1, the methacryloyl chloride is slowly added at a speed such that it is completely added within 25-30 minutes.
[0026] Furthermore, the defoaming agent in step S3.2 is BYK024 aqueous defoaming agent.
[0027] Furthermore, the wetting agent in step S3.2 is BYK-2012 water-based dispersible wetting agent.
[0028] An antistatic waterborne polyurethane floor slurry is prepared by the above-mentioned method for preparing the antistatic waterborne polyurethane floor slurry.
[0029] The beneficial effects are as follows: 1. The present invention prepares amino-modified Ti-MOF by using 2-aminoterephthalic acid and tetrabutyl titanate in N,N-dimethylformamide and anhydrous ethanol, then dissolves polydopamine in N,N-dimethylformamide, adds copper benzoyl acetone and amino-modified Ti-MOF for electrostatic spinning and high-temperature carbonization to obtain nano antibacterial and antistatic fibers. During the electrostatic spinning process, the amino and organic ligands in the amino-modified Ti-MOF with a high specific surface area, the amino and phenolic hydroxyl groups of the polydopamine, and the copper in the copper benzoyl acetone The interaction between ions and organic ligands forms a complex with high cross-linking density and stable structure under the action of hydrogen bonds and coordination reactions, which ensures the uniformity and stability of the fibers in the metal organic nanofiber membrane. In the subsequent carbonization process, it can not only form a conductive network with carbon nanofibers as the matrix and uniform load of Ti and Cu metal particles and a stable structure, giving the subsequent water-based polyurethane excellent antistatic ability, but also by controlling the amount of nitrogen introduced during the high-temperature carbonization process, partial TiO2 and CuO are generated, while enhancing the antibacterial properties of the subsequent water-based polyurethane.
[0030] 2. The present invention modifies guar gum by using methacryloyl chloride, and then fully disperses the guar gum with the nano antibacterial antistatic fiber in deionized water to obtain an antibacterial antistatic organic filler dispersion. The methacryloyl chloride undergoes an esterification reaction with the hydroxyl group in the guar gum, thereby replacing the hydroxyl group in the guar gum with the methacryloyl group. The acryloyl group can be compounded with the nano antibacterial antistatic fiber, thereby improving the compatibility of the nano antibacterial antistatic fiber and preventing uneven distribution caused by migration in the polyurethane, thereby improving the conductive property of the waterborne polyurethane and further improving the antistatic ability. Then, the waterborne polyurethane is cross-linked with the waterborne polyurethane under the action of ethylenediamine to form a three-dimensional network, thereby increasing the cross-linking degree between the polyurethane and the compressive strength and wear resistance of the waterborne polyurethane.
[0031] The invention adds a reaction solution into an antibacterial and antistatic organic filler dispersion, then adds ethylenediamine for post-chain extension reaction, and simultaneously introduces the antibacterial and antistatic organic filler, wherein the modified guar gum is cross-linked with the waterborne polyurethane under the action of ethylenediamine, and the cross-linking reaction is carried out during the chain extension reaction of the waterborne polyurethane, so that a stronger three-dimensional structure can be formed in the polyurethane network, and the compressive strength and wear resistance of the waterborne polyurethane are further improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The present invention is a flow chart of a method for preparing an antistatic waterborne polyurethane floor slurry used in an embodiment of the present invention. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1: An antistatic waterborne polyurethane floor slurry and a preparation method thereof, such as Figure 1 As shown, the following steps are included:
[0035] S1: Preparation of nano antibacterial and antistatic fibers;
[0036] S1.1: N,N-dimethylformamide and anhydrous ethanol are mixed in a volume ratio of 1:1 in a container, stirred at a stirring speed of 200 rpm, and then 4 wt% of 2-aminoterephthalic acid is added. After stirring for 20 minutes, tetrabutyl titanate is added, and the volume of tetrabutyl titanate accounts for 2.5% of the total volume of N,N-dimethylformamide and anhydrous ethanol. Then, the mixture is placed in an ultrasonic disperser and ultrasonically dispersed at an ultrasonic frequency of 25 kHz for 10 minutes. Then, the mixture is heated in an oven at 150°C for 18 hours, washed twice with N,N-dimethylformamide and anhydrous ethanol respectively, and then dried by rotary evaporation to obtain amino-modified Ti-MOF;
[0037] S1.2: 6 parts of polydopamine and 50 parts of N,N-dimethylformamide were placed in a container and stirred until the polydopamine was completely dissolved, and then 8 parts of copper benzoyl acetone and 12 parts of amino-modified Ti-MOF were added, and ultrasonic dispersion was performed in an ultrasonic disperser at an ultrasonic frequency of 35 kHz for 8 minutes, and then magnetic stirring was performed at a rotation speed of 150 rpm for 6 hours to obtain a metal organic spinning solution;
[0038] S1.3: Load the metal organic spinning solution into the injection pump of the electrospinning machine. The inner diameter of the injection pump needle is 0.4mm. Adjust the distance between the injection pump needle and the aluminum foil receiving plate to 10cm. Then perform electrospinning at a working voltage of 12kV and a spinning speed of 0.02mm / min. Collect the metal organic nanofiber membrane on the aluminum foil receiving plate, put it in an oven and dry it at 75°C for 10 hours. Then place it in a tubular furnace. Pass 85% of the volume of the tubular furnace into nitrogen and adjust the temperature to 200°C. Heat for 1 hour, then increase the temperature to 850°C at a heating rate of 8°C / min, and keep it warm for 40 minutes to obtain nano antibacterial and antistatic fibers.
[0039] S2: preparing antibacterial and antistatic organic filler dispersion;
[0040] S2.1: 15 parts of deionized water are placed in a container, and then placed in an ice water bath at 2°C, 3 parts of guar gum are added and stirred evenly, 1 part of methacryloyl chloride is added within 25 minutes, and the mixture is transferred to room temperature and stirred at a stirring speed of 100 rpm for 18 hours, and then dried in an oven at 70°C to obtain modified guar gum;
[0041] S2.2: Mix 4 parts of nano antibacterial antistatic fiber and 1 part of polyvinyl pyrrolidone and place them in a container, add 120 parts of deionized water and stir evenly, then add and place in an ultrasonic homogenizer, and perform ultrasonic treatment at an ultrasonic power of 400 W for 20 minutes to obtain a nano antibacterial antistatic fiber dispersion, then add 2 parts of modified guar gum to the nano antibacterial antistatic fiber dispersion, continue to perform ultrasonic treatment at an ultrasonic power of 600 W for 8 minutes to obtain an antibacterial antistatic organic filler dispersion.
[0042] S3: Cross-linked composite of waterborne polyurethane and antibacterial and antistatic filler;
[0043] S3.1: 40 parts of castor oil and 13 parts of isophorone diisocyanate were mixed uniformly and allowed to stand at 85°C for 2 hours, then 2.5 parts of 2,2-dihydroxymethylbutyric acid were added and stirred for 3 hours, then the temperature was lowered to 45°C, and then 2 parts of triethylamine were added and stirred for 32 minutes to obtain a reaction solution;
[0044] S3.2: Add the reaction solution obtained in step S3.1 to the antibacterial and antistatic organic filler dispersion obtained in step S2.2 and stir evenly, then add 0.8 parts of ethylenediamine, 0.05wt% of BYK024 aqueous defoamer and 0.1wt% of BYK-2012 aqueous dispersant wetting agent, place in a basket grinder and stir at a speed of 1800rpm for 1 hour to obtain an antistatic waterborne polyurethane floor slurry.
[0045] Example 2: An antistatic waterborne polyurethane floor slurry and a preparation method thereof, such as Figure 1 As shown, the following steps are included:
[0046] S1: Preparation of nano antibacterial and antistatic fibers;
[0047] S1.1: N,N-dimethylformamide and anhydrous ethanol are mixed in a volume ratio of 1:1.05 in a container, stirred at a stirring speed of 200 rpm, and then 6 wt% of 2-aminoterephthalic acid is added. After stirring for 20 minutes, tetrabutyl titanate is added, and the volume of tetrabutyl titanate accounts for 3% of the total volume of N,N-dimethylformamide and anhydrous ethanol. Then, the mixture is placed in an ultrasonic disperser and ultrasonically dispersed at an ultrasonic frequency of 25 kHz for 10 minutes. Then, the mixture is heated in an oven at 150°C for 18 hours, washed twice with N,N-dimethylformamide and anhydrous ethanol respectively, and then dried by rotary evaporation to obtain amino-modified Ti-MOF;
[0048] S1.2: 8 parts of polydopamine and 60 parts of N,N-dimethylformamide were placed in a container and stirred until the polydopamine was completely dissolved. Then, 10 parts of copper benzoyl acetone and 15 parts of amino-modified Ti-MOF were added, and the mixture was placed in an ultrasonic disperser for ultrasonic dispersion at an ultrasonic frequency of 35 kHz for 8 minutes, and then magnetically stirred at a rotation speed of 150 rpm for 6 hours to obtain a metal organic spinning solution.
[0049] S1.3: Load the metal organic spinning solution into the injection pump of the electrospinning machine. The inner diameter of the injection pump needle is 0.4mm. Adjust the distance between the injection pump needle and the aluminum foil receiving plate to 10cm. Then perform electrospinning at a working voltage of 12kV and a spinning speed of 0.02mm / min. Collect the metal organic nanofiber membrane on the aluminum foil receiving plate, put it in an oven and dry it at 75°C for 10 hours. Then place it in a tubular furnace. Pass 85% of the volume of the tubular furnace into nitrogen and adjust the temperature to 200°C. Heat for 1 hour, then increase the temperature to 850°C at a heating rate of 8°C / min, and keep it warm for 40 minutes to obtain nano antibacterial and antistatic fibers.
[0050] S2: preparing antibacterial and antistatic organic filler dispersion;
[0051] S2.1: 20 parts of deionized water are placed in a container, and then placed in an ice water bath at 2°C, 4 parts of guar gum are added and stirred evenly, 1.5 parts of methacryloyl chloride are added within 25 minutes, and the mixture is transferred to room temperature and stirred at a stirring speed of 100 rpm for 18 hours, and then dried in an oven at 70°C to obtain modified guar gum;
[0052] S2.2: Mix 6 parts of nano antibacterial antistatic fiber and 1.5 parts of polyvinyl pyrrolidone and place them in a container, add 150 parts of deionized water and stir evenly, then add and place in an ultrasonic homogenizer, and perform ultrasonic treatment at an ultrasonic power of 400 W for 20 minutes to obtain a nano antibacterial antistatic fiber dispersion, then add 3 parts of modified guar gum to the nano antibacterial antistatic fiber dispersion, continue to perform ultrasonic treatment at an ultrasonic power of 600 W for 8 minutes to obtain an antibacterial antistatic organic filler dispersion.
[0053] S3: Cross-linked composite of waterborne polyurethane and antibacterial and antistatic filler;
[0054] S3.1: 42 parts of castor oil and 13.5 parts of isophorone diisocyanate were mixed uniformly and allowed to stand at 85°C for 2 hours, then 3 parts of 2,2-dihydroxymethylbutyric acid were added and stirred for 3 hours, then the temperature was lowered to 45°C, and then 2.3 parts of triethylamine were added and stirred for 32 minutes to obtain a reaction solution;
[0055] S3.2: Add the reaction solution obtained in step S3.1 to the antibacterial and antistatic organic filler dispersion obtained in step S2.2 and stir evenly, then add 1 part of ethylenediamine, 0.1wt% of BYK024 aqueous defoamer and 0.3wt% of BYK-2012 aqueous dispersant wetting agent, place in a basket grinder and stir at a speed of 1800 rpm for 1 hour to obtain an antistatic waterborne polyurethane floor slurry.
[0056] Example 3: An antistatic waterborne polyurethane floor slurry and a preparation method thereof, such as Figure 1 As shown, the following steps are included:
[0057] S1: Preparation of nano antibacterial and antistatic fibers;
[0058] S1.1: N,N-dimethylformamide and anhydrous ethanol are mixed in a volume ratio of 1:1 in a container, stirred at a stirring speed of 250 rpm, and then 4 wt% of 2-aminoterephthalic acid is added. After stirring for 30 minutes, tetrabutyl titanate is added, and the volume of tetrabutyl titanate accounts for 2.5% of the total volume of N,N-dimethylformamide and anhydrous ethanol. Then, the mixture is placed in an ultrasonic disperser and ultrasonically dispersed at an ultrasonic frequency of 30 kHz for 15 minutes. Then, the mixture is heated in an oven at 155°C for 20 hours, washed with N,N-dimethylformamide and anhydrous ethanol for 3 times respectively, and then dried by rotary evaporation to obtain amino-modified Ti-MOF;
[0059] S1.2: 6 parts of polydopamine and 50 parts of N,N-dimethylformamide were placed in a container and stirred until the polydopamine was completely dissolved, and then 8 parts of copper benzoyl acetone and 12 parts of amino-modified Ti-MOF were added, and ultrasonic dispersion was performed in an ultrasonic disperser at an ultrasonic frequency of 40 kHz for 10 minutes, and then magnetic stirring was performed at a rotation speed of 200 rpm for 8 hours to obtain a metal organic spinning solution;
[0060] S1.3: Load the metal organic spinning solution into the injection pump of the electrospinning machine. The inner diameter of the injection pump needle is 0.5mm. Adjust the distance between the injection pump needle and the aluminum foil receiving plate to 15cm. Then perform electrospinning at a working voltage of 15kV and a spinning speed of 0.03mm / min. Collect the metal organic nanofiber membrane on the aluminum foil receiving plate, put it in an oven and dry it at 80℃ for 12 hours. Then place it in a tubular furnace. Pass 90% nitrogen gas of the tubular furnace volume into the tubular furnace and adjust the temperature to 250℃. Heat for 1.5 hours, then increase the temperature to 900℃ at a heating rate of 10℃ / min. Keep warm for 50 minutes to obtain nano antibacterial and antistatic fibers.
[0061] S2: preparing antibacterial and antistatic organic filler dispersion;
[0062] S2.1: 15 parts of deionized water are placed in a container, and then placed in an ice water bath at 4°C, 3 parts of guar gum are added and stirred evenly, 1 part of methacryloyl chloride is added within 30 minutes, and the mixture is transferred to room temperature and stirred at a stirring speed of 120 rpm for 20 hours, and then dried in an oven at 75°C to obtain modified guar gum;
[0063] S2.2: Mix 4 parts of nano antibacterial antistatic fiber and 1 part of polyvinyl pyrrolidone and place them in a container, add 120 parts of deionized water and stir evenly, then add and place in an ultrasonic homogenizer, and perform ultrasonic treatment at an ultrasonic power of 500 W for 25 minutes to obtain a nano antibacterial antistatic fiber dispersion, then add 2 parts of modified guar gum to the nano antibacterial antistatic fiber dispersion, continue to perform ultrasonic treatment at an ultrasonic power of 800 W for 10 minutes to obtain an antibacterial antistatic organic filler dispersion.
[0064] S3: Cross-linked composite of waterborne polyurethane and antibacterial and antistatic filler;
[0065] S3.1: 40 parts of castor oil and 13 parts of isophorone diisocyanate were mixed uniformly and allowed to stand at 90°C for 2.5 hours, then 2.5 parts of 2,2-dihydroxymethylbutyric acid were added and stirred for 3.5 hours, then the temperature was lowered to 50°C, and then 2.3 parts of triethylamine were added and stirred for 40 minutes to obtain a reaction solution;
[0066] S3.2: Add the reaction solution obtained in step S3.1 to the antibacterial and antistatic organic filler dispersion obtained in step S2.2 and stir evenly, then add 0.8 parts of ethylenediamine, 0.05wt% of BYK024 aqueous defoamer and 0.3wt% of BYK-2012 aqueous dispersant wetting agent, place in a basket grinder and stir at a speed of 2000rpm for 1.5 hours to obtain an antistatic waterborne polyurethane floor slurry.
[0067] Comparative Example 1: The difference from Example 1 is that in Comparative Example 1, the polydopamine in step S1.2 is replaced with an equal mass of polyacrylonitrile, and the remaining steps are the same as those in Example 1 to prepare an antistatic water-based polyurethane floor slurry, which is recorded as Comparative Example 1.
[0068] Comparative Example 2: The difference from Example 1 is that in Comparative Example 2, the copper benzoyl acetonate in step S1.2 is replaced with copper chloride with the same copper ion mass, and the remaining steps are the same as those in Example 1 to prepare an antistatic water-based polyurethane floor slurry, which is recorded as Comparative Example 2.
[0069] Comparative Example 3: The difference from Example 1 is that Comparative Example 3 removes step S2.1 and does not add modified guar gum in step S2.2. The remaining steps are the same as those in Example 1 to prepare an antistatic water-based polyurethane floor slurry, which is recorded as Comparative Example 3.
[0070] Comparative Example 4: The difference from Example 1 is that, in Comparative Example 4, 0.8 parts of ethylenediamine are directly added to the reaction solution, and the mixture is stirred for 30-40 minutes to obtain an aqueous polyurethane. The aqueous polyurethane is then added to the antibacterial and antistatic organic filler dispersion obtained in step S2.2 and stirred evenly. 0.05wt% of BYK024 aqueous defoamer and 0.1wt% of BYK-2012 aqueous dispersing wetting agent are added, and the mixture is placed in a basket grinder and stirred at a speed of 1800-2000rpm for 1-1.5 hours to obtain an antistatic aqueous polyurethane floor slurry, which is recorded as Comparative Example 4.
[0071] Experiment 1: Take the antistatic waterborne polyurethane floor slurry prepared in Examples 1-3 and Comparative Examples 1-4, and perform performance tests according to the standard of GB / T22374-2018 floor coating materials. The wear resistance is tested under the conditions of abrasion machine with an abrasion mass of 750g and a rotation of 500r. The compressive strength is tested within 24h and 7d, and the data is recorded and tabulated, as shown in Table 1.
[0072] Table 1: Performance of antistatic waterborne polyurethane floor slurry
[0073]
[0074] It can be seen from the data of Examples 1-3 in Table 1 that the antistatic waterborne polyurethane floor slurry has low surface resistance and volume resistance, and has excellent hardness, wear resistance and compressive strength. It can be seen from the data of Comparative Examples 1-2 that when polydopamine is replaced with polyacrylonitrile, the conductivity, hardness, wear resistance and compressive strength are all reduced, proving that there is an interaction between the amino group and organic ligand in the Ti-MOF of this embodiment, the amino group and phenolic hydroxyl group of polydopamine, and the copper ion and organic ligand in copper benzoyl acetone, which can improve the conductivity and strength of the waterborne polyurethane floor slurry.
[0075] It can be seen from the data of Examples 1-3 and Comparative Example 3 in Table 1 that the absence of modified guar gum has a significant effect on the hardness, wear resistance and compressive strength of the antistatic waterborne polyurethane floor slurry. This proves that modified guar gum can increase the degree of crosslinking with polyurethane and improve the compressive strength and wear resistance of the waterborne polyurethane floor slurry.
[0076] It can be seen from the data of Examples 1-3 and Comparative Example 4 in Table 1 that the hardness, wear resistance and compressive strength of the finally obtained water-based polyurethane floor slurry are reduced by first preparing the water-based polyurethane and then cross-linking it with the antibacterial and antistatic organic filler. This proves that the cross-linking reaction during the chain extension reaction of the water-based polyurethane can form a more solid three-dimensional structure in the polyurethane network, further improving the compressive strength and wear resistance of the water-based polyurethane.
[0077] Experiment 2: The antistatic waterborne polyurethane floor slurry prepared in Example 1-3 was evenly coated on the surface of the corrugated paper using a laboratory coating machine, and dried naturally at room temperature. After the coating was completely dried, it was sterilized by ultraviolet for 30 minutes to obtain a coating sample. A meat extract peptone agar medium was prepared and sterilized, and then poured into a sterilized culture dish to obtain a plate; 10 μL of Escherichia coli suspension (10 7 CFU / mL) and 10 μL of Staphylococcus aureus suspension (1×10 8 CFU / mL), the number of viable bacteria N before contact was determined by plate counting method, and 10 μL of Escherichia coli suspension (1×10 8 CFU / mL) and 10 μL of Staphylococcus aureus suspension (1×10 8 CFU / mL) were smeared on the surface of the coating samples respectively, so that the relative humidity in the plate was not less than 90%, and incubated at 37℃ under light. After 1 hour, the bacterial solution on the surface of the coating sample was resuspended with sterile saline, and then dripped on the plate, and evenly spread with a sterile triangular stick. The number of live bacteria on the plate was calculated and recorded as N1. The sterilization rate n%=(N-N1) / N×100%. The higher the sterilization rate, the better the antibacterial performance, as shown in Table 2.
[0078] Table 2: Sterilization rate of floor slurry
[0079]
[0080] It can be seen from the data in Table 2 that the antistatic waterborne polyurethane floor slurry prepared in Examples 1-3 has a sterilization rate of up to 98% against Staphylococcus aureus and a sterilization rate of up to 99% against Escherichia coli within 1 hour, which proves that the antistatic waterborne polyurethane floor slurry prepared in the examples has good antibacterial properties.
[0081] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing an antistatic waterborne polyurethane floor slurry, characterized in that: The following steps are involved: S1: Preparation of nano antibacterial and antistatic fibers After N,N-dimethylformamide and anhydrous ethanol are uniformly mixed, 2-aminoterephthalic acid is added, and then tetrabutyl titanate is added for ultrasonic dispersion, heated and washed, and then dried to obtain amino-modified Ti-MOF, polydopamine is dissolved in N,N-dimethylformamide, benzoyl acetone copper and amino-modified Ti-MOF are added, ultrasonically dispersed and stirred, and then electrostatic spinning and high-temperature carbonization are performed in sequence to obtain nano antibacterial and antistatic fibers; S2: Preparation of antibacterial and antistatic filler dispersion Add guar gum to deionized water in an ice water bath, then add methacryloyl chloride, then transfer to room temperature for stirring, and dry to obtain modified guar gum, ultrasonically disperse nano antibacterial antistatic fiber and polyvinyl pyrrolidone in deionized water, then add modified guar gum for ultrasonic dispersion to obtain antibacterial antistatic organic filler dispersion; S3: Cross-linked composite of waterborne polyurethane and antibacterial and antistatic filler Mix castor oil and isophorone diisocyanate and let stand, then add 2,2-dihydroxymethylbutyric acid and stir. After cooling, add triethylamine and stir. Then add it to the antibacterial and antistatic organic filler dispersion and stir evenly. Then add ethylenediamine, defoaming agent and wetting agent, and stir at high speed to obtain an antistatic waterborne polyurethane floor slurry.
2. The method for preparing an antistatic waterborne polyurethane floor slurry according to claim 1, characterized in that: Step S1: Preparation of nano antibacterial and antistatic fibers, comprising the following steps: S1.1: N,N-dimethylformamide and anhydrous ethanol are mixed in a container at a volume ratio of 1: (1-1.05), stirred at a stirring speed of 200-250 rpm, and then 4-6 wt% of 2-aminoterephthalic acid is added. After stirring for 20-30 minutes, tetrabutyl titanate is added, and then placed in an ultrasonic disperser, ultrasonically dispersed at an ultrasonic frequency of 25-30 kHz for 10-15 minutes, and then heated in an oven at 150-155 ° C for 18-20 hours, washed with N,N-dimethylformamide and anhydrous ethanol for 2-3 times, and then rotary evaporated to obtain amino-modified Ti-MOF; S1.2: 6-8 parts of polydopamine and 50-60 parts of N,N-dimethylformamide are placed in a container and stirred until the polydopamine is completely dissolved, and then 8-10 parts of copper benzoyl acetone and 12-15 parts of amino-modified Ti-MOF are added, and ultrasonic dispersion is performed in an ultrasonic disperser at an ultrasonic frequency of 35-40 kHz for 8-10 minutes, and then magnetic stirring is performed at a rotation speed of 150-200 rpm for 6-8 hours to obtain a metal organic spinning solution; S1.3: Load the metal organic spinning solution into the injection pump of the electrospinning machine, adjust the distance between the needle of the injection pump and the aluminum foil receiving plate to 10-15cm, and then perform electrospinning at a working voltage of 12-15kV and a spinning speed of 0.02-0.03mm / min, collect the metal organic nanofiber membrane on the aluminum foil receiving plate, put it into an oven and dry it at 75-80℃ for 10-12 hours, then place it in a tubular furnace, introduce 85-90% nitrogen gas of the tubular furnace volume into the tubular furnace and adjust the temperature to 200-250℃, heat for 1-1.5 hours, then heat to 850-900℃ at a heating rate of 8-10℃ / min, and keep warm for 40-50 minutes to obtain nano antibacterial and antistatic fibers.
3. The method for preparing an antistatic waterborne polyurethane floor slurry according to claim 2, characterized in that: Step S2 is to prepare an antibacterial and antistatic organic filler dispersion, comprising the following steps: S2.1: 15-20 parts of deionized water are placed in a container, and then placed in an ice water bath at 2-4°C, 3-4 parts of guar gum are added and stirred evenly, and then 1-1.5 parts of methacryloyl chloride are slowly added, and after transferring to room temperature, stirring at a stirring speed of 100-120 rpm for 18-20 hours, and then drying in an oven at 70-75°C to obtain modified guar gum; S2.2: Mix 4-6 parts of nano antibacterial antistatic fiber and 1-1.5 parts of polyvinyl pyrrolidone and place them in a container, add 120-150 parts of deionized water and stir evenly, then add and place in an ultrasonic homogenizer, perform ultrasonic treatment at an ultrasonic power of 400-500W for 20-25 minutes to obtain a nano antibacterial antistatic fiber dispersion, then add 2-3 parts of modified guar gum to the nano antibacterial antistatic fiber dispersion, continue to perform ultrasonic treatment at an ultrasonic power of 600-800W for 8-10 minutes to obtain an antibacterial antistatic organic filler dispersion.
4. The method for preparing an antistatic waterborne polyurethane floor slurry according to claim 3, characterized in that: Step S3, cross-linking and compounding of waterborne polyurethane and antibacterial and antistatic filler, comprises the following steps: S3.1: 40-42 parts of castor oil and 13-13.5 parts of isophorone diisocyanate are uniformly mixed and allowed to stand at 85-90°C for 2-2.5 hours, and then 2.5-3 parts of 2,2-dihydroxymethylbutyric acid are added and stirred for 3-3.5 hours, and then the temperature is lowered to 45-50°C, and then 2-2.3 parts of triethylamine are added and stirred for 32-40 minutes to obtain a reaction solution; S3.2: Add the reaction solution obtained in step S3.1 to the antibacterial and antistatic organic filler dispersion obtained in step S2.2 and stir evenly, then add 0.8-1 parts of ethylenediamine, 0.05-0.1wt% of defoaming agent and 0.1-0.3wt% of wetting agent, place in a basket grinder and stir at a speed of 1800-2000rpm for 1-1.5 hours to obtain an antistatic waterborne polyurethane floor slurry.
5. The method for preparing an antistatic waterborne polyurethane floor slurry according to claim 2, characterized in that: The volume of tetrabutyl titanate added in step S1.1 accounts for 2.5-3% of the total volume of N,N-dimethylformamide and anhydrous ethanol.
6. The method for preparing an antistatic waterborne polyurethane floor slurry according to claim 2, characterized in that: The inner diameter of the needle of the syringe pump in step S1.3 is 0.4-0.5 mm.
7. The method for preparing an antistatic waterborne polyurethane floor slurry according to claim 3, characterized in that: The methacryloyl chloride is slowly added in step S2.1 at a rate such that it is completely added within 25-30 minutes.
8. The method for preparing an antistatic waterborne polyurethane floor slurry according to claim 4, characterized in that: The defoamer in step S3.2 is BYK024 aqueous defoamer.
9. The method for preparing an antistatic waterborne polyurethane floor slurry according to claim 4, characterized in that: The wetting agent in step S3.2 is BYK-2012 water-based dispersed wetting agent. 10.An antistatic waterborne polyurethane floor slurry, characterized in that: The antistatic waterborne polyurethane floor slurry is prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Metal / carbon nano composite fiber derived based on MOFs (Metal Organic Frameworks) as well as preparation method and application of metal / carbon nano composite fiber
CN114875525A
Carbon nanofiber composite material, self-supporting electrode, battery, preparation method and application
CN117988098A